2020
DOI: 10.1111/liv.14411
|View full text |Cite
|
Sign up to set email alerts
|

HSD17B13 as a promising therapeutic target against chronic liver disease

Abstract: See Article on Page 889

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 22 publications
1
11
1
Order By: Relevance
“…20 Recent findings have demonstrated that selective targeting of HSD17B13 mRNA in hepatocytes might be a promising therapeutic approach in NASH. 35,36 Although the HSD17B13 variant did not modify liver phenotypes in our patients, it affected testosterone and SHBG levels in the Polish and German cohorts respectively. A similar finding i.e., a lower testosterone levels, was previously described in male patients with advanced chronic liver disease.…”
Section: Discussioncontrasting
confidence: 54%
“…20 Recent findings have demonstrated that selective targeting of HSD17B13 mRNA in hepatocytes might be a promising therapeutic approach in NASH. 35,36 Although the HSD17B13 variant did not modify liver phenotypes in our patients, it affected testosterone and SHBG levels in the Polish and German cohorts respectively. A similar finding i.e., a lower testosterone levels, was previously described in male patients with advanced chronic liver disease.…”
Section: Discussioncontrasting
confidence: 54%
“…The present study is the first extending the association between HSD17B13 and protection against chronic liver disease to an Asian population, namely Pakistani. Our data are consistent with those reported for other ethnicities and, together with them, underline the potential of HSD17B13 as a therapeutic target [41] to treat liver disease irrespective of ethnicity, and its role in the genetic susceptibility to chronic liver disease.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is desirable to investigate the underlying mechanisms of lean NAFLD and provide advice for its treatment and related drug development. As a protective allele for various liver diseases, HSD17B13 rs72613567 is considered to be an attractive target for therapeutic drug development [38,39]. Our results here showed that the effect of HSD17B13 rs72613567 in lean NAFLD differs from that in non-lean NAFLD, which implications for drug development and personalized treatment for lean NAFLD.…”
Section: Discussionmentioning
confidence: 64%